Fine‐scale genetic structure and helping decisions in a cooperatively breeding bird - Leedale, Amy E.; Sharp, Stuart P.; Simeoni, Michelle; Robinson, Elva J. H.; Hatchwell, Ben J. (Molecular ecology, 2018)
In animal societies, characteristic demographic and dispersal patterns may lead to genetic structuring of populations, generating the potential for kin selection to operate. However, even in genetically structured populations, social interactions may still require kin discrimination for cooperative behaviour to be directed towards relatives. Here, we use molecular genetics and long‐term field data to investigate genetic structure in an adult population of long‐tailed tits Aegithalos caudatus, a cooperative breeder in which helping occurs within extended kin networks, and relate this to patterns of helping with respect to kinship. Spatial autocorrelation analyses reveal fine‐scale genetic structure within our population, such that related adults of either sex are spatially clustered following natal dispersal, with relatedness among nearby males higher than that among nearby females, as predicted by observations of male‐biased philopatry. This kin structure creates opportunities for failed breeders to gain indirect fitness benefits via redirected helping, but crucially, most close neighbours of failed breeders are unrelated and help is directed towards relatives more often than expected by indiscriminate helping. These findings are consistent with the effective kin discrimination mechanism known to exist in long‐tailed tits and support models identifying kin selection as the driver of cooperation.